"Accompanied Only by My Thoughts": A Kantian Perspective on Autonomy at the End of Life. Issue 6 (23rd December 2022) - Elsner, Anna Magdalena; Rampton, Vanessa
Abstract: Within bioethics, Kant's conception of autonomy is often portrayed as excessively rationalistic, abstract, and individualistic, and, therefore, far removed from the reality of patients' needs. Drawing on recent contributions in Kantian philosophy, we argue that specific features of Kantian autonomy remain relevant for medical ethics and for patient experience. We use contemporary end-of-life illness narratives—a resource that has not been analyzed with respect to autonomy—and show how they illustrate important Kantian themes, namely, the duty to know oneself, the interest in elaborating universalizable principles, and the emphasis on ideals as points of orientation that guide behavior without ever being fully realized. As Kant does, the patient-authors discussed here perceive the end of life as a moment to reflect on the constitutive principles which have governed that life, thereby offering a privileged moment to pursue self-knowledge. We argue that bioethical conceptions of autonomy stand to gain if they revise their conception of Kantian moral philosophy as too formal, abstract, and detached from emotions and personal relationships to be helpfully applied.